If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6(k + 2) = 3(2k + -5) Reorder the terms: 6(2 + k) = 3(2k + -5) (2 * 6 + k * 6) = 3(2k + -5) (12 + 6k) = 3(2k + -5) Reorder the terms: 12 + 6k = 3(-5 + 2k) 12 + 6k = (-5 * 3 + 2k * 3) 12 + 6k = (-15 + 6k) Add '-6k' to each side of the equation. 12 + 6k + -6k = -15 + 6k + -6k Combine like terms: 6k + -6k = 0 12 + 0 = -15 + 6k + -6k 12 = -15 + 6k + -6k Combine like terms: 6k + -6k = 0 12 = -15 + 0 12 = -15 Solving 12 = -15 Couldn't find a variable to solve for. This equation is invalid, the left and right sides are not equal, therefore there is no solution.
| 47=4x+10+7x-7 | | 15=5(3x-10)-5x | | -6.8(4x+6)-1.7(3x-5)= | | 16y=112 | | 3(80x-9x)=x-96 | | 8a-6a+3=7 | | 16=12-x | | 3m-9n=2 | | 2g-5=6 | | 2z-3=4z-1 | | 6a^2+12a-48=0 | | 36=3x+2+6x+7 | | (2x+5)8=72 | | -36-52= | | 4.5-1.5(6m+2)=3 | | 7+3*4-1=39 | | 3y-4(y+2)=2(3y-2) | | -1-10(10r+6)= | | -3n-5n=8 | | 5x^2+5y=45 | | 3z-9=3 | | -2x+6=16 | | 7p=35 | | (x-5)(x-6)=6 | | 4x-7=7x-5 | | x^4-17x^2+52=0 | | 3a-15=-6 | | 3y/2=-6 | | 4x+20=53-2x | | y=7x^2-x+11 | | V^2-2v=4v+40 | | 17=(3x) |